Capabilities of Police Investigators in Solving Rape Cases in Q: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
AbstractRape has long been a contentious issue in our culture, but it wasn't a focus of mainstreamresearch until the 1970s, when the feminist movement gained momentum, and society'sawareness of the gender gap increased. Rape then became a hot topic in criminological,sociological, and psychological literature. The general public anticipates fairness from thepolice and expects them to be unbiased. Victims anticipate that the police will treat theircomplaints fairly when they come to them for assistance. It should be mandated that policeprovide survivors with reports.The most significant indicator of training is whether or not a police investigator follows SOPs,which are the rules, procedures, and benchmarks required for a company to flourish. The bestability of a police investigator to solve rape cases is to be honest when resolving crimes and tonot be partial while gathering evidence. While the capacity of a police investigator to solveproblems with curiosity appears to be the least significant talent of an investigator in solvingrape cases. A lack of technical proof, such as CCTV cameras, a lack of evidence to support aninquiry, lying or making blatantly false statements on a major topic, and the absence of awitness. Furthermore, conducting seminars for awareness of rape cases in the vicinity ofpolice stations and creating ads to educate the community.
Keywords: Criminology